PENINGKATAN MINAT MAHASISWA BERWIRAUSAHA - Yayan Sudrajat (Sosio e-Kons, 2015)
The purpose of this study was to analyze student interest in entrepreneurship, especially about the factors that affect student interest, constraints, and the type of business that is interested in entrepreneurship. This study is a survey research with a descriptive approach. Population is a student entrepreneurship courses numbered 237 seventh semester students of Indonesian Language and Literature Faculty of Language and Arts University Indraprasta PGRI Jakarta. The sampling technique is random sampling was conducted on 50 students. Data were collected using a questionnaire. Likert scale is used to measure based on student opinion about the motivation for starting a business, a report on the characteristics and habits of behavior related to business relationships and organizations. Keywords : interests, Students, entrepreneur